A Comparative Study of Functional and Non Functional Parameter on Advanced IoT Deployment Tools - Deepak Mangal, Akhilesh Kumar Singh, Juginder Pal Singh (International Journal of Advanced Science and Technology, 2020)
Now days Internet of Things has become one of the most trending technology in the field of Computer Science. Many businesses are accepting the various practices of Internet of Things to bring reliability, stability and security in their development and production phases of products or services. Deploying their application to a large scale is the key challenge faced by many users. Choosing the right tool according to the needs is a decision one should make taking various parameters into consideration. This paper studies various deployment tools, based on various researches and practices, on platforms like Raspberry pi board, Linux devices and so on and tried to give a uniformed comparative study among them on various useful and important parameters.